2018
DOI: 10.1371/journal.pbio.2005536
|View full text |Cite
|
Sign up to set email alerts
|

The noisy basis of morphogenesis: Mechanisms and mechanics of cell sheet folding inferred from developmental variability

Abstract: Variability is emerging as an integral part of development. It is therefore imperative to ask how to access the information contained in this variability. Yet most studies of development average their observations and, discarding the variability, seek to derive models, biological or physical, that explain these average observations. Here, we analyse this variability in a study of cell sheet folding in the green alga Volvox, whose spherical embryos turn themselves inside out in a process sharing invagination, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 87 publications
3
51
0
Order By: Relevance
“…1c) during type-B inversion in Volvox globator is mainly driven by contraction of parts of the cell sheet [17]. This contraction is regulated separately from the earlier invagination of the cell sheet, and therefore indicative of a transition towards higher developmental complexity within Volvocaceae [17]. The present result that type-A inversion does not rely on this additional deformation mode lends further support to this inference.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…1c) during type-B inversion in Volvox globator is mainly driven by contraction of parts of the cell sheet [17]. This contraction is regulated separately from the earlier invagination of the cell sheet, and therefore indicative of a transition towards higher developmental complexity within Volvocaceae [17]. The present result that type-A inversion does not rely on this additional deformation mode lends further support to this inference.…”
Section: Discussionsupporting
confidence: 76%
“…By contrast, we have previously shown that the peeling of the anterior hemisphere ( Fig. 1c) during type-B inversion in Volvox globator is mainly driven by contraction of parts of the cell sheet [17]. This contraction is regulated separately from the earlier invagination of the cell sheet, and therefore indicative of a transition towards higher developmental complexity within Volvocaceae [17].…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Most studies in developmental biology have focused on deciphering molecular and cellular mechanisms that regulate the average behavior of developmental processes, with less attention paid to variability in these processes. However, more and more evidence shows that developmental processes exhibit considerable intrinsic vari-ability at the molecular and cellular levels, such as in gene expression (Burga et al, 2011;Raj et al, 2010), cell proliferation (Fang and Yuste, 2017), growth (Hong et al, 2016), differentiation, and morphogenesis (Haas et al, 2018). Systems-level analysis of the sources, properties, and implications of developmental variability will provide an important perspective to understand the establishment and maintenance of developmental reproducibility.…”
Section: Introductionmentioning
confidence: 99%